(untitled) (The Journal of Psychology and Sociology, 2017)
This study is aimed at the diagnosis of the types of relation to pregnancy and the image of the child, implied a certain degree of readiness for motherhood, as well as at identifying plants in the upbringing and development of the child. In the study of the pregnant women were used such methods as a test “Figures”, aimed at the diagnosis of the types of relation to pregnancy and the image of the child, color test of rela tions by M. Etkind; questionnaire aimed at identifying plants in the upbringing and development of the child); questionnaire “Creating a parent sphere” focused on the identification of the information on the specifics of the course of ontogeny of maternal sphere; projective technique “Family figure”; PARI technique, allowing to diagnose installation on education. This theme seems relevant in connection with the observed today processes of transformation of traditional values, in particular, family, procre ation and child rearing. The sample amounted to pregnant women in the amount of 50 people, average age is 26 years. The results of the application of a projective test “Figures”, led to the conclusion that the majority of women is characterized by a predominance of anxiety and ambivalent parent relationships (58%). At the same time in some of the subjects (30%) is observed readiness for motherhood, 9% of women have the ignoring type of parent relations. The results of the questionnaires and interviews regarding the ontogeny of maternal sphere indicate the presence in a sample of women, maternal sphere of which is characterized by a lack of formation. The data obtained in the processing of the survey results, aimed at determining the education systems, are a sign of commitment of the tested women committed to a specific regime, as well as the lack of focus on the severity of the child’s development.